Rationale for participation in venous leg ulcer clinical research: Patient interview study. Issue 6 (13th July 2020) - Weller, Carolina D.; Richards, Catelyn; Turnour, Louise; Team, Victoria
Abstract: Recruitment to wound care clinical trials is challenging and a better understanding of patient decisions to participate has the potential to influence recruitment success. We conducted 31 semi‐structured telephone interviews of patients who participated in the Aspirin in Venous Leg Ulcer (ASPiVLU) randomised controlled trail (RCT) or ASPiVLU cohort study. Data were coded and analysed using thematic analysis. We identified four key themes: (a) "I participated to help others"; (b) "I participated in research to thank those who cared for me"; (c) "I participated to receive better care"; and (d) "I participated to have a say on what works." These themes became basic elements for the Rationale for Research Participation Framework that we have developed to improve the participant recruitment process for clinical trials in wound care.